Arhetip modrega starca v sodobni ukrajinski prozi: diahroni vidik - Bashkyrova, Olga; Gaidash, Anna; Lutsiuk, Mykola (Slavia Centralis, 2021)
The paper tackles the representations of the wise old man archetype in modern Ukrainian literature. The authors study the semantic field generated by the archetype in biblical tradition. In the framework of Jungian theory, mythopoetic and semiotic insight, as well as postcolonial and gender studies, the features of the archetype representation in the Ukrainian literature of the 20thand 21st centuries are outlined. The findings prove that the representations of the wise old man embody integration of the self-awareness of a postcolonial subject, demonstrate him/her as an agent of historical memory, and form a specific narrative center connecting the disparate parts of reality. The correlation of the archetype functions with the generic structure of the modern Ukrainian prose (mystical and adventure novel, family saga) is detected.